Perancangan Switch Control Battery Charger Pada Pembangkit Listrik Tenaga Hybrid Sebagai Suplai Beban Rumah Pedesaan - Marpaung, Noveri Lysbetti; Yohanes, Edwin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Using of hybrid plant among battery, photovoltaic (PV) and generator for people in a remote area, can be a solution to overcome shortage of electrical energy caused by the electrical energy company cant not acces it. The aim of this riset is to make a prototype by desaining a switch control battery charger on hybrid plant for suplaying load(s) from households in rural. The Generator and photovoltaic are used to charge battery and supply load(s), while the battery used to supply the load only. There are three electric sources for supplying the load(s), there for, a switch control needed to choose which source will supply the load(s). The main priority of switch control consecutively is battery ,PV,and generator. Controlling it uses a microcontroller ATMega 8535 as relay controller, to connect or disconnect electrical source for suplying battery and load(s), base on voltage examided by a voltage censor. The Minimum limit to supply the load is 10.7 VDC for battery, 18 VDC for photovoltaic. On the other side, generator needs 209 VAC to supply the load. The measuring of voltage censors produce an average error around 0.61%. This prototype works well as it’s framework by controlling the switch control from three different sources to supply the load automatically, based onvoltage used microcontroler.Keywords : Photovoltaic, Battery, Generator, Microkontroler ATMega 8535, Hybrid Plant